2016
DOI: 10.1097/olq.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Anal Dysplasia Screening and Treatment in a Southern Human Immunodeficiency Virus Clinic

Abstract: Background Persistent human papillomavirus infection in human immunodeficiency virus (HIV)-infected individuals has been strongly associated with anal squamous cell carcinoma. The incidence of anal squamous cell carcinoma continues to increase in this population despite advances in HIV therapy. There are few studies describing the prevalence of anal cancer precursors, treatment outcomes, and associated factors among HIV-infected populations in the southern United States. Methods A retrospective chart review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In this prospective study of HIV+ MSM undergoing a screening/treatment program for anal mucosa dysplasic lesions, the presence of �high-grade anal intraepithelial lesions were related to infection by HPV genotypes 11 16, 18, 53, 61 and 68, a low CD4 nadir and a history of AIDS. This finding of a relationship between HSIL-positivity and poor immunological status is consistent with previous observations that prolonged antiretroviral treatment [21][22][23] and a high CD4 count, regardless of CD4 nadir [24], are protective factors against HSIL. A recent prospective study observed a similar incidence of HPV-16 and -18 genotypes in the anal PLOS ONE mucosa of French HIV+MSM, but HPV-16 was more persistent and therefore more closely correlated with the presence of HSIL [25].…”
Section: Discussionsupporting
confidence: 92%
“…In this prospective study of HIV+ MSM undergoing a screening/treatment program for anal mucosa dysplasic lesions, the presence of �high-grade anal intraepithelial lesions were related to infection by HPV genotypes 11 16, 18, 53, 61 and 68, a low CD4 nadir and a history of AIDS. This finding of a relationship between HSIL-positivity and poor immunological status is consistent with previous observations that prolonged antiretroviral treatment [21][22][23] and a high CD4 count, regardless of CD4 nadir [24], are protective factors against HSIL. A recent prospective study observed a similar incidence of HPV-16 and -18 genotypes in the anal PLOS ONE mucosa of French HIV+MSM, but HPV-16 was more persistent and therefore more closely correlated with the presence of HSIL [25].…”
Section: Discussionsupporting
confidence: 92%
“…All other authors declare no competing interests. (22, 23, 30-32, 34-36, 38, 41-43, 85-101) N populations 29 18 17 6 8 4 N PLHIV 7750 5311 4487 1107 2505 1745 ASCUS-AIN1+ prevalence (26-28, 32-35, 102-126) N populations 37 28 20 10 11 2 N PLHIV 8790 6782 5342 1720 2198 351 HSIL-AIN2+ prevalence (30,31,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137) N populations 23 15 16 6 5 7…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Willeford et al have noted significantly less follow-up with young black men, which is associated with higher rates of high-grade anal dysplasia. 16 Failure to follow up with SCCA would also lead to lower survival.…”
Section: Discussionmentioning
confidence: 99%